Study of fetomaternal outcome in twin pregnancy - Rami, Bijal D.; Kaul, Somika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Twin pregnancy being one of the causes of high-risk pregnancy is associated with both maternal and fetal complications. This study aims at analysing the fetal and maternal outcome in such cases. All cases were studied according to their parity, maternal age, fetal presentation, mode of delivery and gestational age. Methods: This prospective study was conducted at one of the tertiary care teaching institutes over a period of one year from January 2018 to December 2018. Out of a total number of 7295 deliveries, 130 were twin pregnancy. It included all women admitted in labour room with clinical or ultrasound diagnosis of twin pregnancy after 20 weeks of gestation. Results: In the present study incidence of twin pregnancy was 1.78%. We observed the highest incidence of twins in the age group of 20-29 years. The least incidence was below the age of 20 years. Incidence of twin pregnancy in our study in primipara was 47.7% and in multipara was 52.3%. Most of the patients (43%) delivered at 32-36 weeks of gestation. Maternal complications were noticed as anemia in 29.2% patients, pregnancy induced hypertension in 55.4% patients, post-partum hemorrhage in 4.6% patients, polyhydramnios in 3.1% patients, premature rupture of membranes in 8.5% patients, gestational diabetes in 0.8% patients and urinary tract infection in 2.3% patients. Majority of the patients delivered vaginally (60.8%), others by lower segment cesarean section (LSCS). In this study 95.8% babies were low birth weight. There were 34 neonatal deaths (13%). Conclusions: Twin pregnancy is a high-risk pregnancy associated with significantly increased maternal morbidity, neonatal morbidity and mortality. Such pregnancies require good antenatal care, early detection of maternal and fetal complications and timely referral to a centre well equipped for management of such cases.